Intelligent food optimization for generation Z using social IoT and the Walrus Optimization Algorithm (WaOA) - Bañuelos Hernández, Karla Fernanda; Ochoa-Zezzatti, Carlos Alberto; Rodríguez Borbón, Manuel Iván (Memorias Científicas y Tecnológicas, 2025)
This project presents an innovative solution aimed at Generation Z, leveraging Social IoT technology and the Walrus Optimization Algorithm (WaOA) to revolutionize meal planning and food management. By integrating an Amazon Echo Show1 0 (3rd Gen) with an Instaview smart refrigerator, the system continuously monitors food inventory, tracks expiration dates, and intelligently suggests meal options, significantly reducing foodwaste. The core of this approach lies in the WaOA, which optimizes meal scheduling by considering multiple factors such as ingredient availability, dietary preferences, expiration dates, and even spatial constraints within the refrigerator. By dynamically adapting to user habits, the system not only enhances efficiency in food consumption but also promotes sustainable eating practices. Ultimately, this project bridges the gap between smart home technology and intelligent resource management, empowering Generation Z to make informed, sustainable food choices while benefiting from an optimized and highly interactive meal-planning experience.